Adrenal Myelolipoma with Haemorrhage - Kumar, Ranjan; Choudhary, Manish Kumar; Bhatnagar, Shorav (Annals of Pathology and Laboratory Medicine, 2020)
Myelolipomas are a rare benign variant of adipose tissue tumors with additional hematopoietic elements. Generally, these tumors were discovered accidentally on autopsy with a low incidence. Adrenal gland is the most common site for myelolipoma. We report a case of adrenal myelolipoma (7 cm) in female in her 4th decade who presented with pain right side abdomen which can be confused with other adrenal malignancy.